Resistance, pacification and consciousness : a discussion of the historiography of Khoisan resistance from 1972 to 1993 and Khoisan resistance from 1652 to 1853 - Abrahams, Yvette (Department of Historical Studies, 2014)
Bibliography: leaves 78-84.